Apulian Karst Springs: A Review - Liso, I.S.; Parise, M. (Journal of Environmental Science and Engineering Technology, 2020)
Apulia (southeastern Italy) is an elongated peninsula, located between the Ionian and the Adriatic seas, characterized by a semi-arid climate. It is an almost entirely karst region, with very limited availability of surface freshwater resources. The groundwater, the only water resource of Apulia, is affected by severe pollution problems related to both antropogenic and seawater intrusion phenomena. This is further exacerbated by the strong tourist vocation of the area, with heavy pressure by touristic water demand, especially during summertime. The Apulian geography and related freshwater problems require a thorough knowledge about karst processes, with specific regard to springs and aquifers. Despite this, in recent decades the attention on regional karst water resources was quite limited, and there is the huge need to implement new research in this field, aimed at reaching a better understanding of the Apulian karst. In this work we present a review on the main Apulian karst springs, divided in the three main sub-karst areas (Gargano, Murge, and Salento), based upon critical revision of the existing scientific literature. The aims are to build a database of known karst springs, and, further, to highlight the widespread and remarkable presence of karst phenomena in the region.